2011
DOI: 10.1017/s0033822200034329
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Distribution of Brazilian Glyptodon SP. Remains: A Direct 14C Date for a Specimen from Iporanga, São Paulo, Brazil

Abstract: ABSTRACT. Glyptodon sp. fossil remains can be found throughout Brazil. However, little information is available about their chronological distribution. With the intention to contribute to this issue, we present, as far as we know, the first direct radiocarbon date for 1 specimen of this genus found in Brazil. The osteoderm MZSP-PV660 found in Abismo do Fóssil Cave

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…These results also indirectly reinforce Holocene survival for megafauna in other South American regions as well (Cione et al, 2001;Rossello et al, 2001;Messineo and Politis, 2009;Steele and Politis, 2009;Cruz et al, 2010). Hubbe et al (2011) from Abismo do Fóssil that is the sole direct date for this genus in Brazil and attests that it lived at least until the LGM in São Paulo State. Besides this date, there are two other direct dates from elsewhere in South America.…”
Section: Continental Chronological Contextmentioning
confidence: 72%
See 3 more Smart Citations
“…These results also indirectly reinforce Holocene survival for megafauna in other South American regions as well (Cione et al, 2001;Rossello et al, 2001;Messineo and Politis, 2009;Steele and Politis, 2009;Cruz et al, 2010). Hubbe et al (2011) from Abismo do Fóssil that is the sole direct date for this genus in Brazil and attests that it lived at least until the LGM in São Paulo State. Besides this date, there are two other direct dates from elsewhere in South America.…”
Section: Continental Chronological Contextmentioning
confidence: 72%
“…Four radiocarbon dates from Abismo do Fóssil Cave were obtained: one undetermined ground sloth species (Tardigrada), one Toxodon platensis, one Eremotherium laurillardi and one Scelidotheriinae. Hubbe et al (2011) recently reported a radiocarbon date for one Glyptodon clavipes from the same cave. The dated remains from the Abismo do Iguatemi Cave come from one Smilodon populator and one Catonyx cuvieri, both found at the lower level of the cave.…”
Section: Sample Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…No entanto, Piló (1998) apresenta uma datação de 77.700±6.100 (técnica U-series) para Hoplophorus euphractus (Minas Gerais), e Hubbe et al (2011), através de 14 C, encontraram para Glyptodon clavipes (São Paulo) uma idade de 20.680-21. 370 anos AP, sendo estas as únicas datações disponíveis no Brasil para esta família até o momento.…”
Section: Discussionunclassified